Once and again : a novel - Serle, Rebecca (Atria Books, 2026)
"Lauren has spent a lot of her life waiting. She spent her childhood on her surfboard, waiting to catch the perfect wave. She waited a long time for her husband Leo. Now she and Leo are together waiting for those two lines on a pregnancy test that will tell Lauren she's finally pregnant. But many women wait for those things. Lauren has also spent her life waiting to use the gift that only the women in her family have: the opportunity, just once, to turn back time and reverse a bad decision, or a moment of catastrophic luck. When Lauren was fifteen, her mother Marcella reversed the car crash that killed Lauren's father, and ever since then, both Marcella and Lauren have been extra cautious around Dave, and perhaps extra brittle with each other. Even though Dave is alive and healthy, and out on the Malibu waves every day. Lauren and Leo's marriage has been rock-steady for the three years they've been married, but their fertility journey is starting to wear on both of them. When Leo takes a six-week job in New York, Lauren temporarily moves back to her childhood house. She'll spend time with her dad, spend time on the water, and try not think about the relationship with her mother she wishes she had. What Lauren doesn't expect is to run into the love of her youth: fellow surfer Stone, back home for the first time in ten years. Since he left and broke Lauren's heart. Now Lauren's thinking about all the choices that have brought her to this moment in her life--and wondering if one of them should be undone." --